Keberagaman Budaya Dalam Bingkai Ketuhanan - Setiawan, Yuda Wira; Albina, Meyniar (Madani: Jurnal Ilmiah Multidisiplin, 2025)
This study examines the relationship between cultural diversity and divine values in fostering social harmony. Cultural diversity, encompassing traditions, customs, and beliefs, is an integral part of Indonesian society, which is grounded in the principle of Belief in One Almighty God. Using a qualitative approach, the research explores how divine values such as tolerance, compassion, and justice serve as a foundation for appreciating cultural diversity while strengthening unity. The findings reveal that integrating divine values into cultural diversity fosters an inclusive, respectful, and harmonious society. However, challenges such as narrow interpretations of religion and cultural conflicts need to be managed wisely. This study provides significant contributions to efforts aimed at promoting a society that upholds diversity within the framework of divinity.